Maker movement: strategy for the construction of knowledge in high school students - Cevallos, María Andrea Mendoza; Cedeño, Ángela María Cevallos; Gámes, María Rodríguez (International research journal of management, IT and social sciences, 2020)
The objective of this work is to identify the characteristics of the Maker movement that facilitate its use as a teaching-learning strategy for the construction of knowledge in high school students. This research was carried out using the desk research methodology, based on evidence from previous application studies of the Maker Movement for the training and motivation of high school students. The Maker philosophy has fostered a new environment for learning based on the theory of constructivism, whose main characteristic is the involvement of students in the creation of artifacts that serve as conductive threads for a series of processes to be carried out that involve cooperation, collaboration and lifelong learning, underpinning processes of experimentation and exploration, in which all phases of the scientific method must be covered, requiring the use of interdisciplinary knowledge, always in a supportive environment. The Maker movement is a catalyst, which promotes learning, with a high dose of motivation, increasing student performance. In Ecuador, mechanisms have been established to promote this culture through the installation and growth of FabLab, in addition to having an increased activity of maker movements in educational institutes.